2024
DOI: 10.1186/s40834-024-00268-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of contraceptives and associated factors among male adolescents in rural secondary schools, Coast Region, Tanzania: a school-based cross-sectional study

Ally Abdul Lyimo,
Jia Guo,
Stella Emmanuel Mushy
et al.

Abstract: Background Teenage pregnancy is still one of the reproductive health concerns facing adolescents in Tanzania. The problem has been associated with physiological, psychological, and social changes and increases the risk of unsafe abortion and adverse maternal, fetal, and neonatal outcomes among adolescents. Low utilization of contraceptive methods among adolescents is one of the key causes. The strategy of involving male adolescents in sexual and reproductive health programs can increase the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This suggest that in order to improve the use of family planning among Tanzanian men increasing education is key. This nding is similar to the ndings reported elsewhere (Lyimo et al, 2024;Wondim et al, 2020) However, the study ndings contradicted with the ndings reported 60% contraceptive use among men in Kibaha, Tanzania (Msovela, 2016). Though the time of the study may have led to this remarkable difference in the prevalence as time differences among the two studies time is six years.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This suggest that in order to improve the use of family planning among Tanzanian men increasing education is key. This nding is similar to the ndings reported elsewhere (Lyimo et al, 2024;Wondim et al, 2020) However, the study ndings contradicted with the ndings reported 60% contraceptive use among men in Kibaha, Tanzania (Msovela, 2016). Though the time of the study may have led to this remarkable difference in the prevalence as time differences among the two studies time is six years.…”
Section: Discussionsupporting
confidence: 82%
“…Majority of population found in rural area (66%), and this showed the need to focus interventions on addressing the contraceptive use challenges encountered by this group on both married (51%) and unmarried (49%) population. The substantial proportion (82%) of the population possessed knowledge of contraception methods indicated a promising likelihood of informed decisionmaking and adoption of family planning methods, potentially leading to a reduction in population growth as reported in other studies (Lyimo et al, 2024;Msovela et al, 2020). This emphasized the importance of education and awareness in promoting contraceptive use and responsible reproductive informed choices (Ochako et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Most studies examining the acceptability of ECs by potential users and health providers have demonstrated acceptance of this method. ECs are generally perceived as particularly useful for adolescents who initiate sexual activity without contraceptive protection and in cases of rape or accidents during the use of other contraceptives [11,16]. According to different studies, IUDs are preferred by women who have given birth [17].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in various countries has revealed a lack of knowledge regarding ECs. Unfortunately, this issue has not been adequately documented in Tanzania[10][11][12]. The primary aim of this study was to analyze the consumption trends of ECs over six consecutive years and provide insights into consumption trends, including exploring the reasons behind the observed fluctuations in consumption.…”
mentioning
confidence: 99%